Relationship Between Mineral Contents and Canopy Reflectance in Washington Navel Orange Trees (Citrus sinensis L. Osbeck) - Kemal Sonmez, Namik; Sari, Mustafa; Sonmez, Sahriye (Asian Journal of Chemistry, 2010)
The aim of this study is to determine the relationship between mineral contents of Washington Navel (Citrus sinensis L. Osbeck) orange trees of different ages and canopy reflectance (RF) of electromagnetic spectrum (EMS) in visible near-infrared region (VNIR). With this aim, nutrients analysis was conducted on orange trees at the ages of 15, 20, 25 and 30 years, which have similar soil properties and similar management techniques. Some spectroradiometric measurements were also carried out. According to the results, the research indicated some important statistical relationships between the RF and the contents of N, P, Mg, Fe, Cu and Zn and also between the normalized difference vegetation index (NDVI) values and the contents of those nutrients in orange trees of different ages. In the study, the most significant relationship appeared in the 25 year old trees. Results show the following relationships in the 25 year old trees; negative between red band and N at p < 0.001 level, positive between red band and P at p < 0.05 level, negative between Mg and blue and red bands at p < 0.05 and p < 0.001 level, positive between Cu and near-infrared bands at p < 0.05 level. In this study, it is determined that there is a positive relationship at p < 0.01 level between the NDVI and N content and positive relationships at p < 0.05 level between NDVI and P, Fe, Cu, Zn contents of 25 year old trees. According to these results, the outcome is that it is more appropriate to prefer 25 year old trees during the studies of remote sensing to measure the contents of nutrients in Washington Navel trees of different ages in the Mediterranean climatic zone.